HOW MOTIVATION WORKS, INDONESIAN EMPLOYEES IN FOREIGN COMPANIES ? - Mochklas, Mochamad; Pinaraswati, Sandra Oktaviana; Setiawan, Teguh (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2018)
To achieve company goals, employees need to be motivated so that they can carry out their duties responsibly and without coercion. The purpose of this study is to find out how employee work motivation works in foreign companies, by knowing the motivation of employees of foreign entrepreneurs can formulate the needs desired by local workers so that their loyalty and performance increases. This research method is descriptive analysis, where the population of this research is employees who work in foreign company South Korea, with sample size 229 people. The results of this study indicate that extrinsic motivation is more dominant influence employee work motivation, employee intrinsic motivation more dominant to fulfill requirement of daily life, and employee extrinsic motivation more dominant to get award.Â